The Cistercian glazed tiles of the Monastery of Alcobaça: characterization of the colour palette. Issue 2 (2nd July 2016) - Carvalho, F.; Coentro, S.; Costeira, I.; Trindade, R.A.A.; Alves, L.C.; da Silva, R.C.; Muralha, V.S.F.
ABSTRACT: The glazed tiles that paved the apse of the Monastery of St. Mary of Alcobaça were a rare decorative element in the most important part of this Cistercian construction. These medieval tiles, all monochromatic, are believed to be a thirteenth-century production and represent some of the first examples of tin-opacified glazed tiles in Christian Portugal. Although lead glazes have been extensively used in medieval pavements in North-Western Europe, opaque tin-glazes are far scarcer. The technology used in this case is a testimony of mixing cultures, combining Cistercian Order traditions of building materials and techniques with the Islamic tin-glazing technology brought to the Iberian Peninsula in the tenth century. These glazes were applied on tiles of several geometric shapes to achieve the final decorative effect. For the first time, these tiles were analytically characterized to determine the chemical composition of the different colours of glaze and these differences were assessed to explain the variety of colours and shades observed. The analytical techniques used were µ-PIXE (micro-particle-induced X-ray emission), µ-Raman spectroscopy and optical microscopy. Samples selected for this study comprise all colours observed in Alcobaça tiles: white, turquoise, brown and several shades of green. Results show that the variety of colours and shades are consistent with different proportions of CuO, Fe2 O3 and SnO2 in a lead-glazed matrix, together with a K-feldspar-rich white inner layer, most likely to be a slip.